The Effects of Neuroinflammation Induced by Typhoid Vaccine on Resting and Task‐Based Electroencephalography - Julia R Plank; Joseph CC Chen; Frederick Sundram; Nicholas Hoeh; Suresh Muthukumaraswamy; Joanne C Lin (Brain and Behavior)
ABSTRACT Introduction Considerable evidence suggests a pathophysiological role of neuroinflammation in psychiatric disorders. Lumbar puncture and positron emission tomography (PET) show increased levels of inflammation in psychiatric disorders. However, the invasive nature of these techniques, as well as their expense, make them undesirable for routine use in patients. Electroencephalography (EEG) is noninvasive, affordable and shows potential as a clinical tool for detection of neuroinflammation. Methods In this randomized, crossover design, placebo‐controlled, double‐blind study, typhoid vaccine was administered to 20 healthy volunteers to induce a low level of neuroinflammation. EEG was recorded before and after placebo/vaccine administration during resting‐state and during performance of the Attention Network Test (ANT). Resting‐state EEG was analyzed using spectral power analysis, and time–frequency analysis was used for the EEG from the ANT. Behavioral data were assessed using linear mixed models and Spearman's correlations. Results Behavioral results from the ANT showed no decrement in performance following the vaccine, consistent with previous studies. During eyes‐open resting, there was a relative decrease in right‐frontal delta power in the vaccine condition compared to placebo. There was a trend toward greater alpha power suppression in the alerting response of the attentional network; however, this finding did not reach significance. Conclusion Decreased resting‐state delta power may reflect an unpleasant internal state conferred by the vaccine. Inflammation did not significantly affect attention networks. The absence of significant alterations may be due to an insufficient inflammatory response. Further studies are needed to assess the feasibility of EEG as a technique for detection of neuroinflammation.